The Oxford encyclopedia of ancient Egypt - Redford, Donald B.,
"Until now, there has been no comprehensive, scholarly English-language encyclopedia covering ancient Egypt. This beautifully constructed work fills that gap with more than 600 academic, but accessible, articles on all aspects of Egyptology. The coverage is interdisciplinary, combining history, archaeology, economics, science, and literary and religious studies. A stunning piece of scholarship."--"Outstanding Reference Sources," American Libraries, May 2002.